THE IMAGE OF BIRDS IN WORLD ARTISTIC THOUGHT (Web of Teachers: Inderscience Research, 2024)
It is known that myths and legends occupy a very important place in world literature. If we look at the literature of any nation, we can see that myths and fairy tales embody the nation's way of life and characteristics. Despite the fact that the main heroes of myths and fairy tales are different in the literature of different nations, they are all images that invite goodness and goodness. Although some of these characters do not exist in real life, it is not an exaggeration to say that they have taken a place in the hearts of many through their characters in fairy tales and legends. Among the mythological images in his literature, one can see common features as well as differences. The image of birds occupies a special place in the oral and written literature of different peoples of the world. Although they differ from each other in appearance and sound, they often attract attention in terms of interpretation in close meanings and similar artistic and aesthetic functions. Among the peoples of the same side of the world, the myths and legends about birds are noteworthy.